KEMAMPUAN REPRESENTASI MATEMATIK SISWA KELAS IX MTS PADA MATERI BANGUN RUANG SISI LENGKUNG DENGAN PENERAPAN PENDEKATAN RECIPROCAL TEACHING - Moka, Santriwati; Hendriana, Heris; Afrilianto, M (IKIP Siliwangi, 2018)
The purpose of this study is to analyze the influence of implementing reciprocal teaching approach as an attempt to improve students’ mathematical representation in class IX-B MTs Al-Musyahadah Cimahi on the curved-face three-dimensional-object. The type of research, which applied, is classroom action research. The classroom action research consists of 2 (two) cycles based on teaching syllabus of the mathematics teacher in class IX-B. Each cycle was conducted based on the learning objectives. The cycle in this study involved the following procedures: (1) Planning; (2) Implementation of action; (3) Observation and evaluation; (4) Reflection. Based on the result of research conducted on the students of class IX-B MTs Al-Musyahadah on the curved-face three-dimensional-object material, it revealed the fact that the use of reciprocal teaching approach can improve the ability of mathematical representation, which are; (1) responses and learning outcomes shown in cycle II are primly good, and (2) the students’ score of mathematical representation test capability in each cycle has improve significantly, until 87% on the last cycle . Moreover, the results showed that there are only 4 students from total 29 students who obtain score below 65. Therefore, Learning by applying reciprocal teaching approach is very effective to use in learning process.